2021
DOI: 10.3390/ani11061729
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative and Apoptotic Pathways in the Testis of Quail Coturnix coturnix during the Seasonal Reproductive Cycle

Abstract: The quail Coturnix coturnix is a seasonal breeding species, with the annual reproductive cycle of its testes comprising an activation phase and a regression phase. Our previous results have proven that the testicular levels of both 17β-estradiol (E2) and androgens are higher during the reproductive period compared to the non-reproductive period, which led us to hypothesize that estrogens and androgens may act synergistically to initiate spermatogenesis. The present study was, therefore, aimed to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 79 publications
(112 reference statements)
0
3
0
Order By: Relevance
“…We speculated that the promotion of apoptosis might be a strategy to eliminate dysfunctional cells arising as a result of HFD‐induced oxidative stress. However, apoptosis might also be induced by the inhibition of the Akt signaling pathway (Falvo et al, 2021; Kang et al, 2020; Wu et al, 2020). Our findings showed that pAkt levels were lower in the corpus of the epididymis of HFD rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculated that the promotion of apoptosis might be a strategy to eliminate dysfunctional cells arising as a result of HFD‐induced oxidative stress. However, apoptosis might also be induced by the inhibition of the Akt signaling pathway (Falvo et al, 2021; Kang et al, 2020; Wu et al, 2020). Our findings showed that pAkt levels were lower in the corpus of the epididymis of HFD rats.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that PCNA is regulated by the Akt signaling pathways in the testis. Specifically, the inhibition of the Akt pathway downregulates the expression of PCNA (Falvo et al, 2021; Lim et al, 2019). The increase in apoptosis and decrease in proliferation in HFD rat epididymis were supported by the reduction in epididymal tissue weight observed in this group.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of these two hormones are strongly correlated since 17-β estradiol is produced via the aromatization of testosterone of the key enzyme P450 aromatase [ 47 , 48 ]. In rats, a daily subcutaneously administration of cocaine hydrochloride (30 or 15 mg/Kg) for a minimum of 72 days induced a decrease in the levels of estrogens (E2), which in males are key hormones in cell differentiation processes, such as spermiohistogenesis [ 49 , 50 , 51 , 52 , 53 ], and at high dose induced an increase in the percentage of spermatozoa having heads separated from the tail [ 54 ]. It was assumed that the reduction in E2 levels was due to decreased body weight rather than a direct drug-related effect.…”
Section: Cocaine and Changes In Fertilitymentioning
confidence: 99%